(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Kishwar Desai as a realistic writer from the Indian soil presented her novels by learning the present condition of women with her background knowledge of her journalistic career. Her novel The Sea of Innocence traces the reality of modern Indian society with the use of advanced technologies and it also highlights the bigotry violence faced by women from dawn to dusk. Desai presents her novel in the detective mode in story telling by presenting the horrific crime committed against the British teenager Liza Kay. Simran Singh as the real dedicated social worker turns as the crime investigator unfolds the mystery of Liza’s death and brings out the curse of modern India with drugs, surreptitious video clippings, corrupted political atmosphere, and eroded the human values. This paper focuses on the menacing darkness created by sadistic criminals towards a girl and the bigotry violence faced by her.